Development and testing of glow-in-the-dark concrete based raised pavement marker for improved traffic safety - Saleem, Muhammad; Hosoda, Akira (Journal of Civil Engineering and Management, 2021)
Road infrastructure has witnessed incremental changes in the past as compared to the immense development witnessed by the vehicle’s safety technology. Bott’s dots and other reflector devices are extensively used on the road infrastructure for lane separation and for improving edge detection. These devices come in a large variety of shapes and sizes, however, all of them fall under the category of retroreflectivity since they depend on vehicle lights to provide reflection. Glow-in-the-dark (GiD) material has the benefit that it can store energy during the presence of light and can emit the stored energy in the form of visible light in the absence of an external light source. In this regard, the presented research work details the development and testing of GiD concrete based markers that can be used for lane separation and edge detection. The benefit of the presented innovation is that GiD concrete based markers can be used for visible light instead of retroreflectivity in addition to acting as a driver alertness tool. The durability performance of the presented innovative GiD based raised pavement markers has been presented along with cost comparison to traditional Bott’s dot. In addition, the presented prototype can be adopted for various architectural and esthetical applications in buildings, parks, walkways and bicycle lanes etc.